Educational Webinars about Online Learning Class - Agustiawati, Hartini (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2022)
Teaching English is a challenging to teacher of English. They must work hard to teach, introduce and persuade students to learn. There are four skills in teaching English, such as listening, speaking, reading and writing. Among them, speaking will be challenging for students. They are afraid to talk and no self confidence to try speaking English. It is totally hard for students who learn English as a Foreign Language. They don’t have a place to practice their English. It makes students lazy to learn and speak English. In this case, teachers must be smart to find strategy or right technique. In order to improve students’ interest and ability a method can be used. As a teacher of English, we must be creative to find out strategy which is suitable to students’ needs.Therefore, Nowadays, we are familiar about online learning class. Teachers must be able to motivate and make class fun in learning online. In order to facilitate teachers to learn and look for the strategy and method, teachers can join Educational webinars